PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU SDS DAN SMPS YAYASAN PENDIDIKAN CENDANA DURI PADA PEMBELAJARAN JARAK JAUH (E-LEARNING) - Naveghia Putri Nadifa; Hendriani Susi; Marzolina Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to find out the effect of work stress and work motivation onteacher performance at the Cendana Duri Elementary School and Cendana Duri JuniorHigh School on E-Learning. The questionnaire was disseminated to 42 respondents andsuccessfully re-collected the complete answers from 42 respondents. Primary data werecollected using questionnaires and to test hypotheses on this study using multiple linearregression analysis with the help of the SPSS program. Data collected from 42respondents were subsequently processed with the help of SPSS software version 26.0using static desk analysisptif and multiple linear regression analysis for generatingclassical assumption tests, data analysis models, coefficient of determination, andhypothesis proofs. The results of this study show that: 1) There was a positive andsignificant effect of work stress and work motivation on teacher performance at theCendana Duri Elementary School and Cendana Duri Junior High School on E-Learning,2) There was no effect of work stress on teacher performance at the Cendana DuriElementary School and Cendana Duri Junior High School on E-Learning, 3) There is apositive and significant effect on teacher performance at the Cendana Duri ElementarySchool and Cendana Duri Junior High School on E-Learning. Keyword: Teachers Performance, Work Stress, Work Motivation